2015
DOI: 10.1002/mds.26378
|View full text |Cite
|
Sign up to set email alerts
|

The motor inhibition system in Parkinson's disease with levodopa‐induced dyskinesias

Abstract: Our study demonstrated that levodopa intake in dyskinetic patients tends to alter the functioning of some parts of the neural network involved in motor inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…Accumulating preclinical experiments indicate a role for the cortex, with LIDs correlating with supersensitive excitatory transmission at corticostriatal synapses and high‐frequency cortical oscillations . Additionally, human neuroimaging studies suggest that abnormal dopaminergic modulation of striato‐cortical networks underlies LIDs, and that alterations in activity of frontal cortex areas were linked to LIDs in PD patients . Dyskinetic patients exhibited decreased activity of the right inferior frontal cortex after l ‐dopa, whereas patients without dyskinesias showed a reverse effect.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating preclinical experiments indicate a role for the cortex, with LIDs correlating with supersensitive excitatory transmission at corticostriatal synapses and high‐frequency cortical oscillations . Additionally, human neuroimaging studies suggest that abnormal dopaminergic modulation of striato‐cortical networks underlies LIDs, and that alterations in activity of frontal cortex areas were linked to LIDs in PD patients . Dyskinetic patients exhibited decreased activity of the right inferior frontal cortex after l ‐dopa, whereas patients without dyskinesias showed a reverse effect.…”
Section: Discussionmentioning
confidence: 99%
“…This task has been employed to explore a range of psychological questions such as the relationship between response initiation and inhibition [26, 27] and the characteristics of inhibitory control [2831]. The stop signal task has also proved useful for characterizing deficits in behavioral inhibition in Parkinson’s disease [32], schizophrenia [33], ADHD [34], and in individuals with alcohol- and drug-dependencies [35, 36]. …”
Section: Motor Inhibition Associated With Action Stoppingmentioning
confidence: 99%
“…This excessive striato-cortical connectivity in response to levodopa may play a role in the pathophysiology of LID [54, 55]. Another study showed that the connectivity of inferior frontal cortex was decreased with M1 and increased with the putamen in patients with LID [56]. This finding suggests that the neural network centered on the inferior frontal cortex may also involve in the pathophysiological mechanisms underlying LID.…”
Section: Intervention-related Network Changesmentioning
confidence: 99%